Spectral subtraction and enhancement for torsional waves propagating in coated pipes. (December 2018) - Duan, Wenbo; Kanfoud, Jamil; Deere, Matthew; Mudge, Peter; Gan, Tat-Hean
Abstract: Ultrasonic guided waves are routinely used for inspection of pipelines. The technique is well established for uncoated pipes where attenuation is very low. However, when the pipe is coated, buried or immersed, sound energy will be absorbed by the coating or radiate into the surrounding medium. Attenuation will increase and the scanning distance will be significantly reduced. The noise level can also increase when the condition of the coating material degrades with age and the bonding condition between pipe and coating becomes unevenly distributed. The increase of attenuation ratio and noise level therefore makes the inspection of ultrasonic waves propagating in coated and buried pipelines particularly difficult. It is often desirable to identify small features amongst the noise floor. To improve signal to noise ratio under these conditions, two techniques are proposed for the study of the propagation of torsional waves in Denso Tape coated pipes. A frequency domain, backward wave cancelling algorithm is used to eliminate the reflected waves coming from the backward direction and clean up the signal. On this basis, a spectral subtraction method is used, which requires knowledge of a small section of pipe that includes no real features, so that the signal from this region provides the characteristic noise signature of the pipe itself. The spectrum of the noise signature is calculated and then subtracted from the total signal using a sliding window technique. Furthermore, a signal region, for instance，the reflected signal from a pipe weld or end, is specified. This represents the characteristic of the incident signal and any signal similar in shape will be enhanced using the sliding window technique. These two techniques serve to reduce the noise floor and enhance small signals that may be buried in it. This is important for ultrasonic non-destructive testing applications in coated and buried pipes.